Hubungan Dukungan Teman Sebaya dengan Tingkat Stres pada Mahasiswa Baru - Muhammad Falihul Husna; Betie Febriana; Wahyu Endang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
First-year university students undergo a transitional phase from the school environment to the academic, social, and emotional demands of higher education. This transition often triggers stress when not supported by an adequate social environment. Peer support plays an essential role in this adaptation process by providing emotional support, information, and a sense of belonging. Positive peer relationships can help students manage academic pressure, whereas poor peer interactions may increase the risk of stress. Therefore, peer support serves as a protective factor in maintaining the psychological well-being of first-year students. This study employed a quantitative approach with a cross-sectional design. Data were collected using the Peer Support Questionnaire (PSQ) and the Student-Life Stress Inventory (SSI) from 130 first-year students of the Faculty of Pharmacy, UNISSULA. The sampling technique used was simple random sampling. Data were analyzed using the Gamma correlation test to determine the relationship between the variables. The Gamma test revealed a p-value of 0.000 (<0.05), indicating that the alternative hypothesis was accepted, meaning there is a significant relationship between peer support and stress levels among first-year students. The correlation coefficient of –0.737 indicates a strong negative relationship, suggesting that higher peer support is associated with lower stress levels. There is a significant and strong relationship between peer support and stress levels among first-year students at the Faculty of Pharmacy, UNISSULA.